Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush. Issue 2 (19th January 2022) - Cong, Feng; Wu, Fu-Yuan; Li, Wen-Chang; He, De-Feng; Sun, Zai-Bo; Huang, Xiao-Ming; Hu, Zhi-Zhong; Zhao, Han
ABSTRACT: The Triassic Lincang granites make up the largest peraluminous granitic batholith in the Changning-Menglian Paleo-Tethys orogenic belt, southeastern Tibetan Plateau. It is undoubtedly very important to investigate the role of crustal magmatism in the evolution of the Changning-Menglian Paleo-Tethys orogenic belt. The Late Triassic Mengsong pluton is composed of strongly peraluminous two-mica monzogranites, and is located in the southernmost part of the Lincang batholith. Despite all being peraluminous granites, they differ markedly in dimensions, petrographic and geochemical characteristics. Mengsong two-mica monzogranites have low contents of TiO2, FeO tot, MgO, and CaO, but high values of SiO2 and Na2 O, compared to biotite monzogranites of the Lincang batholith. The Lincang biotite monzogranites show an enrichment in light rare earth elements (LREE) and weak Eu anomalies (δEu = 0.3–0.8). However, the Mengsong two-mica monzogranites show a clear tetrad effect and contain pronounced negative Eu anomalies (δEu = 0.1–0.3). Geochemical compositions and mineral textures of two-mica monzogranites indicate that they are of highly fractionated type affinity. The two-mica monzogranites are characterized by negative εHf ( t ) values (−9.3 to −1.7) and εNd ( t ) values (−9.6 to −7.9), while the biotite monzogranites have lower εHf ( t ) values (−15.5 to −6.1) and εNd ( t ) values (−14.5 to −11.5). Isotopic compositions suggest that they were cogenetic and derived from partial melting of the lower crust. Our petrogenetic and zircon U–Pb age data support models that relate the Lincang and Mengsong granites to post-collisional magmatism in the Changning-Menglian Paleo-Tethys orogenic belt during the Middle to Late Triassic. We interpret the Mengsong pluton to represent highly fractionated melts from crystal mush reservoirs and the Lincang granites to be complementary residual. Graphical Abstract: uf0001